Renewable Energy : Evaluation of the World Bank Group’s Support for Electricity from Renewable Energy Resources, 2000-2017 - Independent Evaluation Group (World Bank, Washington, DC, 2020)
The Clean Energy Transition—the pathway for decarbonizing global energy—is essential to foster inclusive and sustainable growth while addressing climate change. Based on EIA forecasts, IEG estimates that annual global financing for RE needs to double, from $300 billion to $600 billion (2017 US$) to meet the SDGs and allow the Clean Energy Transition. The WBG’s RE investment portfolio of $22 billion over the evaluation period, 2000–2017, included support across all major RE technologies. Based on 168 evaluated RE projects (101 WB, 60 IFC, 7 MIGA) during FY00–FY17, the WBG overall had a 66% success rate—varying across institutions (71% WB, 51% IFC, 86% MIGA).